2018
DOI: 10.18203/2320-1770.ijrcog20184489
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of ectopic pregnancy in a tertiary care hospital

Abstract: Background: Ectopic pregnancy is a life-threatening emergency commonly encountered by medical practitioner. Diagnosis is frequently missed and should be considered in any women in the reproductive age group with abdominal pain or vaginal bleeding. The aim of the study is to assess the incidence, clinical presentation, risk factors, methods of diagnosis, treatment, outcome and complications.Methods: This was a prospective study at S.C.B. Medical college from January to December 2017. Parameters like age, parity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
7
10
0
Order By: Relevance
“…6,18,22,26 Similarly, ampullary part of the tube was commonly involved in most of the ectopic pregnancies in various other studies. 13,[15][16][17][19][20][21]23,28,29 The right side was more frequent than the left which was consistent with different other studies. 16,18,21,23,26,29 Our hospital being a tertiary level referral centre, 60.2% of the women had ruptured ectopic pregnancies which is comparable to most of the studies ranging from 56% to 91.5%.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…6,18,22,26 Similarly, ampullary part of the tube was commonly involved in most of the ectopic pregnancies in various other studies. 13,[15][16][17][19][20][21]23,28,29 The right side was more frequent than the left which was consistent with different other studies. 16,18,21,23,26,29 Our hospital being a tertiary level referral centre, 60.2% of the women had ruptured ectopic pregnancies which is comparable to most of the studies ranging from 56% to 91.5%.…”
Section: Discussionsupporting
confidence: 86%
“…13,[15][16][17][19][20][21]23,28,29 The right side was more frequent than the left which was consistent with different other studies. 16,18,21,23,26,29 Our hospital being a tertiary level referral centre, 60.2% of the women had ruptured ectopic pregnancies which is comparable to most of the studies ranging from 56% to 91.5%. 4,13,17,19,21,26 Since most of the patients had ruptured ectopic pregnancy, they required emergency laparotomy and salpingectomy (81.8%) as life saving measures.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Behera et al reported 54.8% in 21-30 years age group. 14 Rate of ectopic pregnancy increased with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Study of Behera A et al, reported association of abortion in 46.2% and tubal ligation in 24.7% cases of ectopic pregnancy. 10 Tubal mucosal damage secondary to infection in abortion hampers the embryo transfer activity and causes ectopic pregnancy. Increased incidences of ectopic pregnancy with tubal ligation are because of the faulty technique, post-partum ligation and failure to achieve hemostasis.…”
Section: Discussionmentioning
confidence: 99%